2020
DOI: 10.1097/sla.0000000000003789
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement on Robotic Mastectomy—Expert Panel From International Endoscopic and Robotic Breast Surgery Symposium (IERBS) 2019

Abstract: Objectives: To achieve a consensus statement on robotic mastectomy. Background: Robotic-assisted surgery has gained much attention especially the results of few case series reporting on the technical feasibility, safety and early oncologic outcomes of robotic-assisted mastectomy in a few centers worldwide. The aim of this consensus statement was to develop and provide standardized guidelines on robotic mastectomy based on consensus statement by a panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 22 publications
0
41
1
1
Order By: Relevance
“…After the preliminary experience of R-NSM with 27 R-NSM ( 27 ), we determined a standardized technique with dissection with non-robotic scissors after sub cutaneous infiltration with adrenaline serum and then robotic dissection through a mono-trocar insert in axillary or lateral small incision ( 26 , 27 ). This technique was reported as the consensus ( 28 ). In this prospective study, we analyzed patients operated on between March 2018 and March 2020, with and without robotic assistance (R-NSM and C-NSM) and IBR with implant breast or latissimus dorsiflap (LDF) with or without association with implant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the preliminary experience of R-NSM with 27 R-NSM ( 27 ), we determined a standardized technique with dissection with non-robotic scissors after sub cutaneous infiltration with adrenaline serum and then robotic dissection through a mono-trocar insert in axillary or lateral small incision ( 26 , 27 ). This technique was reported as the consensus ( 28 ). In this prospective study, we analyzed patients operated on between March 2018 and March 2020, with and without robotic assistance (R-NSM and C-NSM) and IBR with implant breast or latissimus dorsiflap (LDF) with or without association with implant.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported a few cases of robotic-NSM (R-NSM) to evaluate feasibility, reproducibility, and safety (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, a technical robotic surgical consensual NSM procedure was reported (28). However, comparison between R-NSM and conventional-NSM (C-NSM) has been recently reported in only one retrospective study with a small sample size and for procedures realized by only one surgeon (29).…”
Section: Introductionmentioning
confidence: 99%
“…Mayo reported their results with NSM over the last decade, showing a decrease in complication rate even with the broadening of indications for the procedure to higher‐risk patients; this confirms a team learning curve for the procedure 60 . Interestingly, the robotic approach to NSM, which was only first reported within the last 3 years, already has several published manuscripts regarding the learning curve 44,61‐63 …”
Section: The Learning Curvementioning
confidence: 86%
“…Endoscopic procedure is an emerging technique that has not yet been fully validated. This allows a NSM with a unique axillary approach with endoscopic or robotic technic, which is now well determined [ 65 ] but contribution of these procedures in comparison with traditional-NSM must be confirmed by prospective studies with analysis of complication rates, aesthetics advantages and cost efficiency. All recent studies about R-NSM showed that this technic could be performed with a brief learning curve [ [14] , [15] , [16] , [17] , [65] , [66] , [67] ].…”
Section: Discussionmentioning
confidence: 99%